Synthesis and biological evaluation of new series of benzamide derivatives containing urea moiety as sEH inhibitors. (15th August 2022) - Tian, Ye; Li, Shuo; Yang, Peiyao; Su, Xiaolu; Liu, Jialu; Lv, Xuening; Dong, Kuan; Yang, Ting; Duan, Meibo; Hu, Guangda; Yue, Hao; Sun, Yanping; et al.
Graphical abstract: Highlights: Benzamide derivatives containing urea moiety were designed and synthesized, and the SAR was explored. Compound B15 exhibited outstanding inhibitory activity against human sEH, with an IC50 value of 0.03 ± 0.01 nM. Compound B15 showed satisfactory metabolic stability in human liver microsomes with a half-time of 197 min. Compound B15 exhibited a better anti-inflammatory and analgesic effect compared to t -AUCB and Celecoxib. Abstract: The pharmacological inhibition of soluble epoxide hydrolase (sEH) was shown to reduce inflammation and pain. Herein, we described a series of newly synthesized sEH inhibitors with the trident-shaped skeleton. Intensive structural modifications led to the identification of compound B15 as a potent sEH inhibitor with an IC50 value of 0.03 ± 0.01 nM. Furthermore, compound B15 showed satisfactory metabolic stability in human liver microsomes with a half-time of 197 min. In carrageenan-induced inflammatory pain rat model, compound B15 exhibited a better therapeutic effect compared to t -AUCB and Celecoxib, which demonstrated the proof of potential as anti-inflammatory agents for pain relief.